On the analysis of the strategic role of intermediate development in the recreation of urban decadent (worn out) districts (fabrics) (case study: metropolis of Tabriz, district 8) - gholamreza jaliz; Karim hoseinzadeh; hosein nazmfar (تحقیقات کاربردی علوم جغرافیایی)
An infill development of the process of urban developing and reusing empty or unused parts or sections of existing urban areas that have already been developed. the infill development, which may be considered as the simplest interpretation of endogenous development, tends to extend development on these lands, with emphasizing the abandoned and empty intra-city lands. Current research with an analytical approach in the infill development with the emphasis on the 8th district of Tabriz Municipality and utilizing statistical-spatial methods has been get involved to this issue. This kind of research is known as descriptive-analytical. the methodology of this research is based on quantitative-spatial approaches. the research method used in this study is a combination of documentary-library methods. in the analytical section, considering the indicators and requirements of infill development in the form of 16 target indicators, the case study and feasibility of infill development in Tabriz 8th district have been discussed. in the current study, to investigate and analyze the strategic role of infill development in regeneration of the urban texture worn of the historical-cultural axis of the metropolitan city of Tabriz, utilizing the geographical information system (GIS) software and Overlapping Functional Analysis, type of weighted overlay and FAHP is done. The results of present study are presented in the form of three priority development plans as well as unauthorized developmental areas.